A Case of Neurocysticercosis Clinically Mimicking Epilepsy: Report from Remote Hilly Area of Bangladesh - Chowdhury, Suman; Uddin, Mohammad Najim (Bangladesh Journal of Infectious Diseases, 2017)
Neurocysticercosis (NCC) is considered a common infection of the nervous system caused by the Taenia solium and is known to be the primary cause of preventable epilepsy in many developing countries. NCC is commonly resulted by the ingestion of Taenia solium eggs after consuming undercooked pork, or contaminated water. The parasite can grow in the brain and spinal cord within the nervous system, causing severe headache and seizures beside other pathological manifestations. People in North Eastern hilly areas of Bangladesh are very much fond of Pork meat. Here in this case report, an elderly indigenous male was found to be presented with weakness and sleep deprivation initially. During subsequent conversation with the patient for obtaining his medical history, he started complaining of dizziness, which eventually led to generalized convulsions lasting for about one minute. Though his neurological system examination was inconclusive, stool routine microscopic examination showed ova of T. solium. IgG antibody against T. solium was positive. Later, the patient was advised to have contrast MRI of brain which revealed multiple Ring enhancing T2 hyperintense cystic lesion with tiny central in different parts of the brain. Bangladesh Journal of Infectious Diseases 2016;3(1):24-27